Forceps, current value - Bazul, Víctor (2015)
I thank the Executive Committee of the First Peruvian Congress of Obstetrics and Gynecology for the honor you have given me to entrust the study of Obstetrics Official Theme entitled Forceps: Present Value; work of the greatest interest in obstetric practice and seek to develop by following a simple plan, classic, recalling that the application of forceps should be a very reasoned act and not a series of mechanical movements learned in a kind of military manual. It should then before applying the forceps in practice to know exactly the services he may or may not pay; enter reasoned discussion of their role and know the purpose of the modifications that have been made to an instrument that day by an advanced degree of perfection reached today.